The Internet addiction among students of primary schools and lower and upper secondary schools and its relation to their level of physical activity - Katarzyna Zuń; Magdalena Zych; Marcin Stanisław Rząca; Katarzyna Kocka (Kazimierz Wielki University, 2017)
Introduction: Physical activity is an important part of a healthy lifestyle, which significantly affects the development of children and youth. Unfortunately, students take less and less physical activity devoting much more time to surfing the Internet. Aim: Determining the relationship between the degree of the Internet addition and the level of physical activity of primary school students and lower and upper secondary school students. Material and methods: The study covered 463 students in the fifth and sixth grades of primary schools and the second and third classes of lower and upper secondary schools.  The research was carried out from February 2017 to April 2017 in schools in Lublin, Radom and nearby villages. The applied research method was a diagnostic survey, and tools: Internet addiction test, Dr. Kimberly Young and the authors' self-designed survey containing questions about physical activity. Results: Dr. Young test pointed out the addiction in 53 out of 463 tested pupils (11.4%). The dependence concerned 12 primary school students (7.9%), 26 lower secondary school students (16.0%) and 15 upper secondary school students (10.0%). In contrast, the risk of addiction occurred in 33 (7.1%) students. Moderate physical activity during the last week for a minimum of 10 minutes 88.8% of respondents declared. Conclusions: • Internet addiction affects the level of physical activity. • The least time for physical activity have those diagnosed with addiction. • It is advisable to undertake educational and activative actions on the forms of leisure time for pupils at all stages of education.